Oral Microbiota Associated with Clinical Efficacy of Ustekinumab in Crohn’s Disease - Xu, Feiyang; Xie, Rui; He, Le; Wang, Honggang; Zhu, Yifan; Yang, Xiaozhong; Yu, Huiming (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
BackgroundCrohn’s Disease (CD) is a chronic inflammatory gastrointestinal disease. Ustekinumab (UST) has been utilized as a therapeutic option for CD patients. However, approximately 40-60% of patients exhibit an inadequate response to UST. Accumulating evidence has confirmed the involvement of oral bacteria in the development of CD. Nevertheless, the relationship between oral microbiota and the efficacy of UST therapy in CD patients has remained unexplored.Materials and MethodsWe recruited 28 healthy individuals and 53 CD patients, 47 of whom completed the entire UST therapy. Oral samples and clinical data were collected. The clinical response and clinical remission were defined based on the CDAI score. Oral samples were analyzed by 16S rRNA gene sequencing. The analysis of sequence data was performed by QIIME and R.ResultsWe revealed the oral microbial difference between the Healthy Control (HC) group and the CD group. The enrichment of Fusobacteria, Leptotrichia, Capnocytophaga, and Campylobacter, and the diminution of Haemophilus and Rothia were observed in the CD group. Differences in oral microbiota were also identified among patients with different efficacy of UST. Compared to the response and remission groups, both the non-response and non-remission groups showed significantly higher levels of Fusobacteria and Leptotrichia. Predictive models for clinical response and clinical remission in UST were developed based on oral microbiota, with the Area Under the Curve (AUC) value of 0.944 and 0.930, respectively.ConclusionOral microbiota was relevant to the UST efficacy in patients with CD based on the predictive model. These findings suggest that oral microbiota could serve as a non-invasive prognostic biomarker for UST treatment in CD patients.
Keywords: Crohn' s disease